2018
DOI: 10.1111/pan.13373
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain management in children: Guidance from the pain committee of the European Society for Paediatric Anaesthesiology (ESPA Pain Management Ladder Initiative)

Abstract: The main remit of the European Society for Paediatric Anaesthesiology (ESPA) Pain Committee is to improve the quality of pain management in children. The ESPA Pain Management Ladder is a clinical practice advisory based upon expert consensus to help to ensure a basic standard of perioperative pain management for all children. Further steps are suggested to improve pain management once a basic standard has been achieved. The guidance is grouped by the type of surgical procedure and layered to suggest basic, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 193 publications
(270 reference statements)
0
74
1
17
Order By: Relevance
“…It can effectively relieve pain intensity, extend the pain-free period, and reduce opioid consumption during the postoperative recovery of adults under general anesthesia [41]. However, no suggestions have been provided in the literature on dexmedetomidine use for reducing postoperative pain in children [40]. Our current findings suggested that dexmedetomidine reduces the number of patients requiring analgesia and the pain intensity among children undergoing strabismus surgery.…”
Section: Plos Onementioning
confidence: 58%
See 1 more Smart Citation
“…It can effectively relieve pain intensity, extend the pain-free period, and reduce opioid consumption during the postoperative recovery of adults under general anesthesia [41]. However, no suggestions have been provided in the literature on dexmedetomidine use for reducing postoperative pain in children [40]. Our current findings suggested that dexmedetomidine reduces the number of patients requiring analgesia and the pain intensity among children undergoing strabismus surgery.…”
Section: Plos Onementioning
confidence: 58%
“…Children undergoing strabismus surgery constitute a very-high-risk group for postoperative pain. Because elevated postoperative pain is associated with EA occurrence, a European Society for Pediatric Anesthesiology Pain Committee guideline [40] suggests postoperative pain management for six frequently performed procedures in children, but not including pediatric strabismus surgery. Dexmedetomidine has analgesic properties and has been widely used in various surgeries in adults.…”
Section: Plos Onementioning
confidence: 99%
“…Meantime of abdominal pain before therapy in our patients was less than a week; however, the recovery time after treating with prednisone was 1.7 days. We were guided by recommendations of European Society for Paediatric Anaesthesiology that the target should be to achieve and maintain pain scores below the intervention threshold of 4 (on a 10-point scale) [16]. Clinically important differences in acute pain relief using patients' perception have an impact on which analgesic interventions are regarded useful.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effective use of basic analgesics has a significant impact on reducing the use of opioids, 63,64 which are reserved for the intraoperative and early postoperative period, in conditions where adequate monitoring is provided and a continuous opioid infusion requires the availability of specially trained personnel 24 h a day. In 2018, the European Society for Paediatric Anaesthesiology (ESPA) Pain Committee published guidelines 65 to improve postoperative pain management in children. Although these guidelines are primarily aimed at Europe, the authors of the guidelines hope that they can also be used in other countries around the world, and that postoperative pain therapy can be adapted based on the availability of medicines, national recommendations and drug registration rules in different countries.…”
Section: Principles Of Pain Management In Childrenmentioning
confidence: 99%